A análise ambiental como subsídio para o desenvolvimento sustentável do município de Capistrano-CE - Bianchi, Christina (2005)
The purpose of this work is the contextual analysis of the present status of the environmental at Capistrano County (Ceará State), producing organized information in order to permit a rational interference on its evolution through proposals subsidizing local and regional Sustainable Development Policies. The methodology adopted in this research was conducted under the optical of the systemic method approach, aiming to analyze the environmental components diagnosis through an interdisciplinary focus. Located at the North region of Ceará State and being part of the Administrative Region of the Baturité Mountain Range, Capistrano has typical resources of semiarid environment and shows a historical predatory agriculture, emphasized by the presence of poor soils, scarce water resources, limited and bad rain distribution, high temperatures and evapo-transpiration and low capacity of water retention in the soil. Historically their natural resources had been used under inadequate way due to economic rashness and to the absence of knowledge on their method of conservation. The diagnosis of on their abiotic, biotic and antropic compounds permitted an evaluation of the present environmental scenario at Capistrano’s County, being useful for the identification of the environmental impact actors, for the evaluation of types and levels of environmental degradation and for the zonation of areas with the same characteristics. From this diagnosis, some preventive or mitigatory actions for the eventual negative impacts imposed by the antropic activities were formulated and a prognostic of the spontaneous evolution of the environment was prepared. The information resulted from the analysis of the present environmental context of the County are important subsidies for the public politics aiming to establish an environmental scenario able to maintain the equilibrium between rational use of natural resources and socio-economic local development. However, the persistence on the present model of agro-cattle exploitation in the County which disregards their natural characteristics is provoking a degeneration process of the ecosystems. The disforestation and the burning of vegetation increase have intensified the erosion process which is evidenced by the presence of wrinkles and rill-erosion. Soils are losing their natural fertility and if this model persists they will lose their productive capacity and by this way there will be the loss the capacity support for any economic activity related to the agriculture sector. Therefore, it is necessary a population change on the thinking and behavior in relation to the use of natural resources or on the contrary the evolution of this figure will be the beginning of the desertification process.